Neuroprotection for ischaemic stroke: translation from the bench to the bedside. - Sutherland, B; Minnerup, J; Balami, J; Arba, F; Buchan, A; Kleinschnitz, C (2012)
Neuroprotection seeks to restrict injury to the brain parenchyma following an ischaemic insult by preventing salvageable neurons from dying. The concept of neuroprotection has shown promise in experimental studies, but has failed to translate into clinical success. Many reasons exist for this including the heterogeneity of human stroke and the lack of methodological agreement between preclinical and clinical studies. Even with the proposed Stroke Therapy Academic Industry Roundtable criteria for preclinical development of neuroprotective agents for stroke, we have still seen limited success in the clinic, an example being NXY-059, which fulfilled nearly all the Stroke Therapy Academic Industry Roundtable criteria. There are currently a number of ongoing trials for neuroprotective strategies including hypothermia and albumin, but the outcome of these approaches remains to be seen. Combination therapies with thrombolysis also need to be fully investigated, as restoration of oxygen and glucose will always be the best therapy to protect against cell death from stroke. There are also a number of promising neuroprotectants in preclinical development including haematopoietic growth factors, and inhibitors of the nicotinamide adenine dinucleotide phosphate oxidases, a source of free radical production which is a key step in the pathophysiology of acute ischaemic stroke. For these neuroprotectants to succeed, essential quality standards need to be adhered to; however, these must remain realistic as the evidence that standardization of procedures improves translational success remains absent for stroke.